Civic engagement as a second-order public good: The cooperative underpinnings of the accountable state - Kenju Kamei; Louis Putterman; Jean-Robert Tyran (Brown University, Department of Economics, 2019)
Effective states provide public goods by taxing their citizens and imposing penalties for non-compliance. However, accountable government requires that enough citizens are civically engaged. We study the voluntary cooperative underpinnings of the accountable state by conducting a two-level public goods experiment in which civic engagement can build a sanction scheme to solve the first-order public goods dilemma. We find that civic engagement can be sustained at high levels when costs are low relative to the benefits of public good provision. This cost-to-benefit differential yields what we call a "leverage effect" because it transforms modest willingness to cooperate into the larger social dividend from the power of taxation. In addition, we find that local social interaction among subgroups of participants also boosts cooperation.
Keywords: C92; D02; D72; H41; 330; civic engagement; public goods provision; punishment; experiment; cooperation